The Effect of Sensory Integration and Treadmill Therapy on Sensory and Behavioral Improvement in Children with Attention Deficit and Hyperactivity Disorder - Chusnul Justanti; Yuly Peristiowati; Nurwijayanti Nurwijayanti (GLOBAL HEALTH SCIENCE GROUP, 2025)
Attention-Deficit Hyperactivity Disorder (ADHD) is a common neuropsychiatric disorder in children, characterized by inattention, hyperactivity, and impulsivity, which significantly impact daily functioning. Sensory Processing Disorder (SPD) is often observed in children with ADHD, affecting their ability to process and respond to sensory stimuli appropriately. Sensory integration therapy and treadmill exercise have been suggested as potential interventions to improve sensory processing and behavioral regulation in children with ADHD. This study aims to evaluate the effect of sensory integration therapy combined with treadmill exercise on sensory processing and behavior in children with ADHD. This was an experimental study with a pre-test and post-test design was conducted with 61 children diagnosed with ADHD. Participants underwent sensory integration therapy and treadmill exercise. Sensory processing and behavioral outcomes were measured using standardized assessments before and after the intervention. Data were analyzed using the Wilcoxon test. Results: The results showed a significant improvement in sensory processing, with pre-test sensory scores averaging 97.62 and post-test scores increasing to 152.90 (p = 0.000). Behavioral outcomes also improved significantly, with pre-test behavior scores of 82.57 decreasing to 67.62 in the post-test (p = 0.000). Sensory criteria shifted from 95.1% in the